Periodontal status and pathogenic bacteria after gastric bypass: a cohort study - Sales-Peres, Sílvia Helena de Carvalho; de Moura-Grec, Patrícia Garcia; Yamashita, Joselene Martinelli; Torres, Elza Araujo; Dionísio, Thiago José; Leite, Celso Vieira de Souza; Sales-Peres, Arsenio; Ceneviva, Reginaldo (Journal of clinical periodontology, 2015)
Aim The aim this study was to evaluate the influence of gastric bypass surgery (GBS) on periodontal disease and quantify the periodontopathogenic bacteria in patients undergoing this surgery. Material and Methods This prospective study was composed of 50 patients who underwent bariatric surgery and the data collection was performed in three periods pre‐operative, 6 (6M) and 12 months (12M) postoperative. The oral clinical examination to assess periodontal disease; gingival fluid sample collection for quantification of the periodontopathogenic bacteria Porphyromonas gingivalis, Tannerella forsythia, Treponema denticola, and Prevotella intermedia using q‐PCR; body mass index (BMI) and for collection of the individual's health‐related data from medical files. Results There was a significant reduction in serum C‐reactive protein (CRP) and glucose levels after surgery. The mean probing pocket depth (PPD) and clinical attachment level (CAL) increased significantly in the postoperative period of 6 months (p = 0.001). In the same period, the amount of P. gingivalis increased (p = 0.028) and the other bacteria decreased slightly (p > 0.050). In the presence of P. gingivalis, T. forsythia, T. denticola and P. intermedia, a poor periodontal condition was observed. Conclusion The periodontal disease increased in severity and P. gingivalis increased after GBS. A systemic inflammation resolution due to bariatric surgery in obese subjects does not seem to affect the course of periodontal disease.